Nigeria's Trend of Military Administration and Economic Decay: An Analytical Review - Abraham Ejogba Orhero; Ugo Chuks Okolie (Universitas PGRI Madiun, 2023)
In contrast to military control, several countries have adopted democracy in recent years. While some research sees the military as a force for modernisation, other studies see democracy as a stepping stone rather than a result of growth. Tribal divides and inequality grew after Nigeria gained independence in 1960 as a result of the British occupiers' dividing of the country. After then, military involvement changed the political climate in Nigeria. This paper explores Nigeria's military governance and economic deterioration from 1960 to 1999 using historical and descriptive analysis. Along with its accomplishments, the military had to overcome significant obstacles including corruption, economic hardships, and human rights violations. The research places emphasis on how the military has developed into a centre for resource exploitation and corruption. Military commanders accumulated huge private fortunes, dominated industries including banking, agriculture, and real estate, and cemented their power in the economy and politics